Effects of maturity and drying method on the nutritive value of tropical grasses in Nicaragua - Hoek, Rein van der; Mena Urbina, Martin A.; Lemus, R; Newman, Y.C; Albrecht K.A (2021)
Tropical grasses are key components for both grazing and conserved forages in sustainable livestock systems (beef and dairy) in Central America. The objective of the study was to evaluate grasses used in Nicaragua and their nutritive value contribution as preserved forage during the dry season under different drying methods. Five tropical bunch grass species were sampled across different farms in Nicaragua in 2014 and 2015 using three replications (Andropogon gayanus, Hyparrhenia rufa, Urochloa brizantha, Megathyrsus maximus, and Cenchrus purpureus). Forage samples were collected at 2, 4, 6, and 8-wk maturity as well as season long samples. Samples drying methods included sun- and oven-dried. Sun-dried samples were air dried outdoors for five days while oven-dried used forced air at 55 oC. Samples were processed to pass a 1-mm screen and analyzed for nutritive value using wet chemistry protocols for crude protein (CP), acid detergent fiber (ADF), neutral detergent fiber (NDF) and in vitro total digestibility (IVTD). Drying methods did not influence CP, ADF, NDF and IVTD concentrations. There were significant differences among grass species in CP levels (P=0.0003), ADF (P=0.0009), and IVTD (P=0.0083). U. brizantha had the greatest CP concentration (79 g/kg) while C. purpureus had the lowest CP (44 g/kg). U. brizantha had the lowest ADF (340 g/kg) concentration relative to the rest of the species. A. gayanus, H. rufa, and Megathyrsus maximus had similar NDF concentrations. In vitro total digestibility ranged from 680 to 750 g/kg with M. maximus having the lowest digestibility. Significant differences in nutritive value were observed among maturity stages for CP (P<0.0001), ADF (P = 0.0022), NDF (P = 0.0006), and IVTD (P=0.0241). Forage species decline markedly with maturity, but U. brizantha maintained greater CP and IVTD concentrations compared other species, indicating that could be a more preferred species for off-season feeding.